On the Resilience of Classes to Change - Vasa, Rajesh; Schneider, Jean-Guy; Nierstrasz, Oscar; Woodward, Clinton (Electronic Communications of the EASST, 2008)
Software systems evolve over time incrementally and sections of code are modified. But, how much does code really change? Lehman’s laws suggest that software must be continuously adapted to be useful. We have studied the evolution of several public domain object-oriented software systems and analyzed the rate as well as the amount of change that individual classes undergo as they evolve. Our observations suggest that although classes are modified, the majority of changes are minor and only a small proportion of classes undergo significant modification.